Theoretical study of heat transfer effects on flow past a parabolic started vertical plate in the presence of chemical reaction of first order - Muthucumaraswamy, Rajamanickam; Velmurugan, Sivasangari (Zielona Góra: Uniwersytet Zielonogórski)
An exact solution of an unsteady flow past a parabolic starting motion of an infinite vertical plate with variable temperature and mass diffusion, in the presence of a homogeneous chemical reaction of first order has been studied. The plate temperature as well as concentration level near the plate are raised linearly with time "t". The dimensionless governing equations are solved using the Laplace-transform technique. The effects of velocity profiles are studied for different physical parameters such as the chemical reaction parameter, thermal Grashof number, mass Grashof number, Schmidt number and time. It is observed that the velocity increases with increasing values of the thermal Grashof number or mass Grashof number. The trend is just reversed with respect to the chemical reaction parameter.
Keywords: parabolic; homogeneous; chemical reaction; first order; vertical plate; heat transfer; mass transfer